Integrated Analysis of Methylome and Transcriptome Changes Reveals the Underlying Regulatory Signatures Driving Curly Wool Transformation in Chinese Zhongwei Goats - Xiao, Ping; Zhong, Tao; Liu, Zhanfa; Ding, Yangyang; Guan, Weijun; He, Xiaohong; Pu, Yabin; Jiang, Lin; Ma, Yuehui; Zhao, Qianjun (Frontiers in Genetics, 2020)
The Zhongwei goat is fed primarily for its beautiful white, curly pelts at around one month old, while this representative phenotype will be disappearing with the less curliness pattern on pelts during postnatal development, which may be mediated by multiple molecular signals. DNA methylation plays important roles in mammalian cellular process and is essential for the initiation of hair follicles (HFs) development. Here, we sought to investigate the effects of genome-wide DNA methylation combining expression profile on underlying curly fleece dynamics. Genome-wide DNA methylation maps and skin transcriptome of skin tissues collected at 45 and 108 days old were determined using whole-genome bisulfite sequencing (WGBS) and RNA sequencing respectively. Between two developmental stages, 1250 out of 3379 differentially methylated regions (DMRs) have been annotated into genes (DMGs), which were mainly related to intercellular communication and cytoskeleton. Integrated analysis of the methylome and transcriptome data identified 14 overlapping genes that are crucial factors for wool fibre development through epigenetic mechanisms. Furthermore, a functional study using human hair inner root sheath cells (HHIRSC) revealed that one of overlapping genes, PDGFC (Platelet-derived growth factor C), had a significant effect on the mRNA expression of several key HF-related genes with enhanced cell migration and proliferation. Our study represents the unprecedented analysis to explore the enigma of fleece morphological changes combining methylome maps and the transcriptional expression and these data revealed stage-specific epigenetic changes that potentially affect the fibre development. Furthermore, our functional study highlights a possible role of overlapping gene PDGFC involved in the HF cells growth, which maybe a predictable biomarker for fur goat selection.